Suggested improved method for the ing-manske and related reactions for the second step of gabriel synthesis of primary amines - Ariffin, Azhar; Yun, C.S.; May, F.Y.; Khan, M.N.; Lan, L.C. (2004)
This work demonstrates an improvement in the Ing-Manske and related procedures by the increase of pH of the reaction mixture after the complete disappearance of N-substituted phthalimide. Hydrazinolysis of N-phenylphthalimide (1a) gave 80% of the desired primary amines after 5.3 h in the absence of added NaOH. The reaction time was reduced to 1.6 h and 1.2 h when 1 eq. and 5 eq. of NaOH were added to the reaction mixture after the complete disappearance of 1a. Hydroxyaminolysis of N-(4-ethylphenyl)phthalimide (1b) gave 80% of the desired primary amines after 7.5 h of reaction time (at added [NaOH] = 0). When 10 eq. and 20 eq. of NaOH were added to the reaction mixture after the disappearance of 1b, the reaction time was reduced to 4 h and 2 h, respectively. Methylaminolysis of N-(2-ethylphenyl)phthalimide (1c) gave 80% of the desired primary amines after 1.7 h (at added [NaOH] = 0). The reaction time was reduced to 1 h and 0.7 h when 1 eq. and 25 eq. of NaOH were added to the reaction mixture after the complete disappearance of 1c.